Eumelanin-releasing spongy-like hydrogels for skin re-epithelialization purposes - Silva, Lucília Pereira (2017)
Melanin function in the skin has been associated with pigmentation but other properties such as electrical conductance, photoprotection, and antioxidant and antimicrobial activity have also been recognized. Nonetheless, the use of melanin in a skin wound healing context has never been considered. In this sense, eumelanin particles with a typical round and nano-sized morphology and electrical conductivity of 2.09 × 10−8 S cm−1 were extracted from the ink of Sepia officinalis. The ability of primary human keratinocytes (hKCs) to phagocyte eumelanin, which was then accumulated in cytosolic vesicles and nuclei surroundings, was demonstrated. Keratinocyte viability and maturation was not affected by eumelanin contact, but at eumelanin amounts higher than 0.1 mg l−1 cell morphology was altered and cell proliferation was inhibited. A time and eumelanin amount-dependent reduction of reactive oxygen species (ROS) released by eumelanin-containing ultraviolet (UV)-irradiated keratinocytes was observed. Eumelanin-containing gellan gum (GG) spongy-like hydrogels allowed a sustained release of eumelanin in the range of 0.1 to 5 mg l−1, which was shown in vitro to not be harmful to hKCs, and the absence of a strong host reaction after subcutaneous implantation in mice. Herein, we propose spongy-like hydrogels as sustained release matrices of S. officinalis eumelanin for predicting a beneficial role in skin wound healing through a direct effect over keratinocytes.